Dose-Dependent Amelioration of Ureteral Obstruction-Induced Kidney Fibrosis by Thymoquinone via GPx-Mediated Antioxidant Defense - Chairil Makky; Suprapti; Muhammad Irsan Saleh; Zulkhair Ali; Novadian (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: Chronic kidney disease inevitably progresses to renal fibrosis, driven heavily by oxidative stress and the depletion of endogenous antioxidants including Glutathione Peroxidase (GPx). Thymoquinone (TQ), a bioactive compound from Nigella sativa, exhibits potent antioxidant properties. This study investigates the dose-dependent efficacy of TQ in mitigating renal fibrosis via GPx modulation in a Unilateral Ureteral Obstruction (UUO) model. Methods: Thirty male Rattus norvegicus were randomly assigned to six groups (n=5): Sham, UUO + olive oil (Negative Control), UUO without oil, and UUO treated with TQ at 5, 10, and 20 mg/kg body weight for 14 days. Renal function (ureum, creatinine) and oxidative stress (Malondialdehyde) were measured. GPx mRNA expression was quantified using Reverse Transcription-Polymerase Chain Reaction. Tubulointerstitial injury (TII) and Positively Stained Area (PSA) for fibrosis were assessed histopathologically. Results: UUO induction significantly downregulated GPx expression (median 0.52 versus 1.40 in Sham, p=0.001) and exacerbated TII (score 3.58) and PSA (11.42%). TQ administration dose-dependently upregulated GPx expression, peaking at 20 mg/kg (median 0.62, p=0.009 versus Negative Control). Furthermore, TQ 20 mg/kg significantly reduced the TII score to 2.26 and decreased fibrotic PSA, ameliorating morphological damage. Conclusion: Thymoquinone exerts potent, dose-dependent antifibrotic and renoprotective effects in obstructive nephropathy by restoring GPx-mediated antioxidant defenses and preventing tubulointerstitial remodeling.